A decision support system for scheduling a vaccination campaign during a pandemic emergency: The COVID-19 case. (March 2023) - Fabbri, Cristiano; Ghedini, Pierfrancesco; Leonessi, Marco; Malaguti, Enrico; Tubertini, Paolo
Abstract: This paper considers the organization and scheduling of a vaccination campaign during a pandemic emergency. We describe the decision process and introduce an optimization model, which showed a powerful multi-scenario tool for scheduling a campaign in detail within a dynamic and uncertain context. The solution of the model gave the decision maker the possibility to test different settings and have a configurable solution within few seconds, compared with the man-days of effort that would have required a manual schedule. Analysis of a real case study on COVID-19 vaccination campaign in northern Italy showed that the use of such optimized solution allowed to cover the target population within a much shorter time interval, compared to a manual approach. Highlights: We consider the organization and scheduling of a vaccination campaign during a pandemic emergency. We describe the decision process and introduce an optimization model to support it. Analysis of a real case study is discussed.